Operative Verbs as a Key for Teaching and Testing Competencies–About Hopes and Disruptive Factors - Keller, Lars (Journal of Geography Education, 2012)
The article at hand refers to results from an evaluation study on the 2009 oral A-level examinations in Geography/History plus International Economic and Cultural Regions at Austrian Commercial Academies (secondary education). It addresses the question of whether the use of operative verbs (= verbs that determine what exactly has to be done when dealing with a task, e.g. describe, analyse etc.) can be a key for successful teaching and examining of competencies at different competence levels. The results stir the hope that systematically organised operator systems may be regarded as rather helpful in the context given, yet a number of disruptive factors can be substantiated as well. Eventually, the question is raised whether the debate on the use of operators and operator systems can really lead to successful, competence oriented teaching and testing without integrating the people involved in the forefront of schooling, students and teachers.
Keywords: Competence oriented teaching and testing, operator systems, levels of competence, factors of interference